Chemical characteristic, lactic acid bacteria population, and angiotensin converting enzyme inhibitory activity of traditional fermented beef ”cangkuk” by spontaneous fermentation with the addition of bamboo shoot - Mirdhayati, I.; Zain, W. N. H. (Diponegoro University, 2020)
This research was conducted to examine the chemical properties, lactic acid bacteria (LAB) populationand angiotensin converting enzyme (ACE) inhibitory activity of fermented beef meat with the addition of bamboo shoots. This research used factorial completely randomized design.Factor A was the preparation method of bamboo shoots: chopped, ground, and extracted. Factor B was the ratio of meat and bamboo shoots (B) which was1:0.75,1:1, 1:1,25ratios. The chemical properties observed were total protein, soluble protein, hydrolysisdegree, pHandtitratableacidity value. The results showed that bamboo shoot preparation methods by ground and extracted were able to reduce total protein, and pH value. The ratio of meat and bamboo shoot (1:0.75 and 1:1) wereable to decreasedtotal protein but increased total titratable acidity. The interaction of the factors A and factor B only occurredin increasing hydrolysisdegree. Both of two factors (A and B) couldnot significantly effect to the number of LAB.The ACE inhibitory activity ranged from 36.5 to 79.6%. It can be concluded that the preparation methods ofbamboo shoots by ground and 1: 0.75 and 1: 1ofbeef : bamboo shoot ratio couldincreasehydrolysis degree and had highest ACE inhibitory activity.